Literature Review: Comparison of the Effectiveness of Reliability-Centered Maintenance and Preventive Maintenance on Cost and Risk - Umarwan, Arie; Pranoto, Hadi (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2025)
The modern industrial era is characterized by the high complexity of systems and the demand for operational efficiency, making maintenance systems play a crucial role in ensuring reliability, safety, and sustainability of production processes. Reliability-Centered Maintenance (RCM) has emerged as a strategic approach to replace conventional Preventive Maintenance (PM) methods, which are often static and inefficient. This study compares the effectiveness of RCM and PM in terms of maintenance cost and risk through a literature review across various industrial sectors, including power generation, automotive, maritime, food and beverage, and energy distribution systems. The results show that RCM implementation can reduce unplanned downtime by up to 55.77%, increase system reliability by 28%, lower maintenance costs from 20% to 70%, and raise system availability from 57% to over 90% in some cases. RCM has also proven to be more adaptive to actual equipment conditions, supports risk-based decision-making, and is more effective in scheduling maintenance for critical assets. Although its implementation requires more data resources and technical expertise, RCM demonstrates superior long-term performance. This study recommends the integration of a hybrid strategy that combines the strengths of RCM, PM, and predictive approaches powered by digital technologies to comprehensively enhance the efficiency and reliability of maintenance systems.